2020
DOI: 10.1152/ajpregu.00040.2020
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metaboreflex-induced increases in effective arterial elastance: effect of heart failure

Abstract: Dynamic exercise elicits robust changes in sympathetic activity in part due to accumulation of metabolites within the active skeletal muscle which activates group III and IV afferents triggering the muscle metaboreflex. This reflex raises cardiac output via tachycardia, increased ventricular contractility, and central blood volume mobilization which improves perfusion to the active skeletal muscle. An important component of maintaining exercise performance is optimal ventricular ‐ vascular coupling which can c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 97 publications
(168 reference statements)
2
19
0
Order By: Relevance
“…After blockade of α‐adrenergic receptors, this coronary vasoconstriction is reversed to coronary vasodilatation during metaboreflex activation, and coronary blood flow increases substantially and there are significant improvements in ventricular function (Coutsos et al., 2010, 2013). Furthermore, we have shown that ventricular–vascular coupling is also markedly altered in heart failure as much greater increases in arterial elastance occurs which are unaccompanied by increases in ventricular elastance thereby further uncoupling an already impaired ventricular–vascular relationship (Mannozzi et al., 2020). The higher the arterial elastance the less effective energy transfer becomes, and this in turn reduces the ability to improve stroke work.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…After blockade of α‐adrenergic receptors, this coronary vasoconstriction is reversed to coronary vasodilatation during metaboreflex activation, and coronary blood flow increases substantially and there are significant improvements in ventricular function (Coutsos et al., 2010, 2013). Furthermore, we have shown that ventricular–vascular coupling is also markedly altered in heart failure as much greater increases in arterial elastance occurs which are unaccompanied by increases in ventricular elastance thereby further uncoupling an already impaired ventricular–vascular relationship (Mannozzi et al., 2020). The higher the arterial elastance the less effective energy transfer becomes, and this in turn reduces the ability to improve stroke work.…”
Section: Discussionmentioning
confidence: 98%
“…During mild exercise (3.2 km h −1 0% grade) increases in ventricular function (d P /d t MAX and d P /d t MIN ) in response to the exercise itself are small. However, the level of increase is not uniform and these small increases in ventricular function do not always reach statistical significance (Kaur et al., 2018; Mannozzi et al., 2020). During muscle metaboreflex activation at mild workload, sympathetic drive to the heart is substantially increased causing highly significant large increases in ventricular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in normal subjects this reflex is thought to become tonically active at relatively modest workloads and activation of this reflex can cause substantial increases in sympathetic activity, which elicits increases in cardiac output via tachycardia, increased ventricular contractility, and central blood volume mobilization (5-7, 9-13, 34-41). Arterial elastance rises in parallel with ventricular maximal elastance, thereby optimizing ventricular-vascular coupling and energy transfer from the left ventricle to the systemic circulation (11,42,43). Peripheral vasoconstriction can also occur which is countered by adrenal epinephrine release and b 2 -mediated vasodilation (16,34,38,40).…”
Section: Introductionmentioning
confidence: 99%
“…However, the baseline value of Ea differed in previous studies due to the different measurements given (19,24,25). Moreover, recent studies reported that a higher Ea dyn might indicate greater efficiency of the cardiovascular system in delivering energy to the arterial system for sustaining blood flow (35,36). Based on this, we were only able to suggest that a higher pre-infusion Ea might indicate a positive preload response to fluid challenge, without using an accurate predictive value.…”
Section: Discussionmentioning
confidence: 79%